Impact of silver substitution on the structural, magnetic, optical, and antibacterial properties of cobalt ferrite - Waqia Tahir; Talat Zeeshan; Salma Waseem; Muhammad Danish Ali; Zohra Kayani; Zill-e-Huma Aftab; Syed Muhammad Talha Mehtab; Safa Ezzine (Scientific Reports, 2023)
Abstract Silver-doped Cobalt Ferrite nanoparticles AgxCo1−xFe2O4 with concentrations (x = 0, 0.05, 0.1, 0.15) have been prepared using a hydrothermal technique. The XRD pattern confirms the formation of the spinel phase of CoFe2O4 and the presence of Ag ions in the spinel structure. The spinel phase AgxCo1−xFe2O4 nanoparticles are confirmed by FTIR analysis by the major bands formed at 874 and 651 cm−1, which represent the tetrahedral and octahedral sites. The analysis of optical properties reveals an increase in band gap energy with increasing concentration of the dopant. The energy band gap values depicted for prepared nanoparticles with concentrations x = 0, 0.05, 0.1, 0.15 are 3.58 eV, 3.08 eV, 2.93 eV, and 2.84 eV respectively. Replacement of the Co2+ ion with the nonmagnetic Ag2+ ion causes a change in saturation magnetization, with Ms values of 48.36, 29.06, 40.69, and 45.85 emu/g being recorded. The CoFe2O4 and Ag2+ CoFe2O4 nanoparticles were found to be effective against the Acinetobacter Lwoffii and Moraxella species, with a high inhibition zone value of x = 0.15 and 8 × 8 cm against bacteria. It is suggested that, by the above results, the synthesized material is suitable for memory storage devices and antibacterial activity.